Log in to add a comment

## Answers

*[2-a+b,b]=[6,2]*

*i.e.,*

2-a+b = 6, b=2

2-a+b = 6, b=2

*substitute b=2 in 2-a+b=6*

*2-a+2 = 6*

*4-a = 6*

*a = 4-6*

*a = -2*Combine all similar variables in the expression.[2-a+b^(2)]=[6,2]

Reorder the polynomial 2-a+b^(2) alphabetically from left to right, starting with the highest order term.[b^(2)-a+2]=[6,2]

Remove the parentheses around the expression b^(2)-a+2.b^(2)-a+2=[6,2]

Remove the parentheses around the expression 6,2.b^(2)-a+2=6,2

Move all terms not containing a to the right-hand side of the equation.-a=-b^(2)-2+6,2

Add 6,2 to -2 to get 60.-a=-b^(2)+60

Multiply each term in the equation by -1.-a*-1=-b^(2)*-1+60*-1

Multiply -a by -1 to get a.a=-b^(2)*-1+60*-1

Simplify the right-hand side of the equation by multiplying out all the terms.a=b^(2)-60